Brain activity underlying the recovery of meaning from degraded speech: a functional near-infrared spectroscopy (fNIRS) study - Wijayasiri, Pramudi; Hartley, Douglas E.H.; Wiggins, Ian M. (Elsevier, 2017)
The purpose of this study was to establish whether functional near-infrared spectroscopy (fNIRS), an emerging brain-imaging technique based on optical principles, is suitable for studying the brain activity that underlies effortful listening. In an event-related fNIRS experiment, normally-hearing adults listened to sentences that were either clear or degraded (noise vocoded). These sentences were presented simultaneously with a non-speech distractor, and on each trial participants were instructed to attend either to the speech or to the distractor. The primary region of interest for the fNIRS measurements was the left inferior frontal gyrus (LIFG), a cortical region involved in higher-order language processing. The fNIRS results confirmed findings previously reported in the functional magnetic resonance imaging (fMRI) literature. Firstly, the LIFG exhibited an elevated response to degraded versus clear speech, but only when attention was directed towards the speech. This attention-dependent increase in frontal brain activation may be a neural marker for effortful listening. Secondly, during attentive listening to degraded speech, the haemodynamic response peaked significantly later in the LIFG than in superior temporal cortex, possibly reflecting the engagement of working memory to help reconstruct the meaning of degraded sentences. The homologous region in the right hemisphere may play an equivalent role to the LIFG in some left-handed individuals. In conclusion, fNIRS holds promise as a flexible tool to examine the neural signature of effortful listening.